2018
DOI: 10.1364/oe.26.018578
|View full text |Cite
|
Sign up to set email alerts
|

Routes of odd-even harmonic emission from oriented polar molecules

Abstract: We study odd-even high-harmonic generation (HHG) from oriented asymmetric molecules with different symmetries in strong laser fields. A model based on strong-field approximations is used which allows us to resolve the contributions of different emission routes to odd-even HHG. The comparison between the HHG yields of all routes versus one certain route demonstrates that the routes in which the electron ionizes from the gerade component of the asymmetric orbital contribute mainly to odd-even HHG. We show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 73 publications
0
7
0
1
Order By: Relevance
“…Specifically, with increasing the ratio Z 1 /Z 2 , the ratio F sharply increases, then approaches or exceeds one, before dropping dramatically. It is noticed that for harmonics near the cutoff, the ratio F undergoes a sharp maximum due to the destructive interference effect and this occurs for odd harmonics and is absent in even ones [23,26]. However, these sharp maximums are not seen in Fig.…”
Section: Iii1 Dependence Of Even-to-odd Ratio On Nuclear-charge Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, with increasing the ratio Z 1 /Z 2 , the ratio F sharply increases, then approaches or exceeds one, before dropping dramatically. It is noticed that for harmonics near the cutoff, the ratio F undergoes a sharp maximum due to the destructive interference effect and this occurs for odd harmonics and is absent in even ones [23,26]. However, these sharp maximums are not seen in Fig.…”
Section: Iii1 Dependence Of Even-to-odd Ratio On Nuclear-charge Ratiomentioning
confidence: 99%
“…6, we plot the ratio F as a function of X. It is shown that, after a sudden growth, the ratio F slowly changes with increasing of X value, except for a sharp maximum due to the destructive interference of odd HHG spectra [23,26]. For harmonics in the plateaus of HHG spectra, and R values as indicated in Fig.…”
Section: Changing the Internuclear Distancementioning
confidence: 99%
See 1 more Smart Citation
“…For aligned symmetric diatomic molecules [31] with a not very large internuclear distance R, it has been shown that the interference of the electronic wave between these two atomic centers of the molecule under the barrier induces the remarkable increase of ionization yields of the target molecule in comparison with its partner atom with a similar ionization potential I p [32][33][34]. Further theoretical studies showed that this effect has important influences on alignment dependence of ATI [35,36], HHG [37] and NSDI [38] of symmetric molecules, as well as ATI and HHG of oriented asymmetric molecules [39].…”
Section: Introductionmentioning
confidence: 99%
“…Sau đó, phương pháp chụp ảnh cắt lớp đã được ứng dụng khi HHG phát xạ khi tương tác với laser hai màu (Zhai et al, 2018). Gần đây, phương pháp chụp ảnh cắt lớp đã được mở rộng cho phân tử bất đối xứng CO (Qin, Zhu, Zhang, & Lu, 2012;Chen, Fu, & Liu, 2013;Xie, Yu, Li, Wang, & Chen, 2018;Zhai et al, 2018;Yuan et al, 2018).…”
unclassified